Transcriptional and Microenvironmental Regulation of Lineage Ambiguity in Leukemia - Hu, Tianyuan; Murdaugh, Rebecca; Nakada, Daisuke (Frontiers in Oncology, 2017)
Leukemia is characterized by the uncontrolled production of leukemic cells and impaired normal hematopoiesis. Although the combination of chemotherapies and hematopoietic stem cell transplantation has significantly improved the outcome of leukemia patients, a proportion of patients still suffer from relapse after treatment. Upon relapse, a phenomenon termed “lineage switch” is observed in a subset of leukemia patients, in which conversion of lymphoblastic leukemia to myeloid leukemia or vice versa is observed. A rare entity of leukemia called mixed-phenotype acute leukemia (MPAL) exhibits co-expression of markers representing two or three lineages. These two phenotypes regarding the lineage ambiguity suggest that the fate of some leukemia retain or acquire a certain degree of plasticity. Studies using animal models provide insight into how lineage specifying transcription factors can enforce or convert a fate in hematopoietic cells. Modeling lineage conversion in normal hematopoietic progenitor cells may improve our current understanding of how lineage switch occurs in leukemia. In this review, we will summarize the role of transcription factors and microenvironmental signals that confer fate plasticity to normal hematopoietic progenitor cells, and their potential to regulate lineage switching in leukemias. Future efforts to uncover the mechanisms contributing to lineage conversion in both normal hematopoiesis and leukemia may pave the way to improve current therapeutic strategies.